Tobias - Erotic Short Story - Jones, S. Jones (Saga Egmont, 2024)
Since turning twenty, Nora and her friends have annually basked under the \\\'Two Moon\\\' - two back-to-back full moon nights - during their traditional valley camping trip. This year however, a surreal encounter flips Nora\\\'s life upside down. Bathed in moonlight by the lake shore, she witnesses an enormous wolf dissolve into the water only to re-emerge in the shape of a man: broad shoulders, a firm torso, and a protruding penis... Carrie S. Jones is a modern American writer who likes to play with different reading genres. From reality to fantasy, crime to romance, she likes to introduce eroticism into every universe. She wants everyone to be able to identify their fantasies, desires and even questions through stories that combine sensuality and ardour. Explore your true nature with this no-holds-barred short story writer.